Efektivitas Kombinasi Agen Pendeplesi Glutathione (GSH) dan Inhibitor Glutathione S-Transferase (GST) pada Resistensi Cisplatin terhadap Sel Kanker: Systematic Literature Review - Nursoleha, Eva; Utami, Wahyu (Journal of Pharmaceutical and Sciences, 2025)
Cisplatin is a platinum-based chemotherapy agent used for the treatment of various types of cancer. However, the use of cisplatin as a chemotherapy agent is limited by drug resistance and side effects due to the formation of inactive metabolites from the conjugation reaction between cisplatin and Glutathione S-Transferase (GST). Thus, Glutathione (GSH) and Glutathione S-Transferase (GST) are essential in controlling cisplatin resistance. This study aims to evaluate the use of a combination of cisplatin with GSH-depleting agents and GST inhibitors to overcome or reduce cisplatin resistance in various cancer cell types in vitro and enhance cisplatin's cytotoxic activity. This research was conducted using a systematic literature review method, with a literature search across two international databases, PubMed and Science Direct, for publications from 2013 to 2024. From 15 selected journals, various GSH-depleting agents and GST inhibitors were found to improve the cytotoxic effects of cisplatin, as analyzed based on data on the levels of GSH and GST in the cells and the percentage of viable cells (% cell viability), which showed a significant decrease. The findings of this study are expected to provide insights into the development of cancer therapies using cisplatin as a chemotherapy agent.